Family and Community Health Medical Residency Program for Hypertense Care - Herrera, Sávia Denise Silva Carlotto; Oliveira, Neilton Araujo de; da Silva, Marcos Gontijo; Herrera, Marcos Renato; Rodrigues, Elizângela Sofia Ribeiro; da Silveira, Janne Marques; Gonçalves, Caio Willer Brito; Rodrigues, Rômulo Lima; Duarte, Rayssa Cláudia Oliveira; Júnior, Júlio Cezar Castro de Souza; Junior, Dilomá Bastos Alves; Araújo, Warly Neves de; et al. (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
The objective of the present study was to evaluate the care provided to patients with systemic arterial hypertension by comparing the basic health units (BHU) of the municipality of Gurupi-TO with and without the family and community health residency program. This is a descriptive, cross-sectional and retrospective research conducted in twelve BHUs. Project approved by the research ethics committee of the University of Gurupi, in which health servants answered the QualiAB assessment and monitoring instrument and the data were tested by the chi-square test to verify if there is a difference in care considering p?5%. or 0,05. Of the 21 items analyzed, 14 obtained better levels in UBS with MRPFCH. Therefore, it is concluded that BHU with MRPFCH, as single health system policies, have better quality in the care of hypertension.